Introduction. From Highbrow to Lowbrow: Studies of Indian B-grade cinema and beyond - Valančiūnas, Deimantas (Acta Orientalia Vilnensia, 2011)
Vilnius University Cardboard skulls decorating the book of the dead’s pink cover―the Necronomicon; intoxicated young ladies having a ‘kitty party’ then gang raping their male servant; secret agents 077 and 707 serving the nation; a shape-shifting monster’s head rotates 180 degrees while tracing a doomed bride in red and the list of similar images is far from exhaustive. The above mentioned aesthetical and narrative cinematic devises just happen to come from a variety of Indian films―usually ascribed to the ‘lower’ cinematic cultures and labeled as exploitative, B-grade or even ‘trash’ cinema. Often despised and ridiculed by academicians, critics, and the big budget film industries while at the same time enjoying vast popularity in smaller urban centers and towns, these Indian low budget films co-exist with Bollywood and other major industries―yet work by their own sets of rules and agendas. These films remain a part of the national as well as global film consumption, even if slightly overshadowed by the blockbuster or Arthouse cinemas. Despite the changing trends in India’s film productions and aesthetics, the low budget cinema retains its cult status throughout the country―and this is most evident while taking a stroll down the Grant Road in Mumbai, lined up with numerous video stalls and offering enormous amounts of cheaply produced ‘3 films in 1’ type of DVDs: the genre selection ranging from action (fight) to horror; from mythological to soft-core sex films.